A politics of health glossary. Issue 7 (13th June 2007) - Bambra, C; Fox, D; Scott-Samuel, A
Abstract : This glossary reflects a (re-)emerging awareness within public health of the political dimension of health and health inequalities, and it also attempts to define some of the key concepts from the political science literature in a way that will be of use in future public health analyses. Examples from different domains (healthcare and population health) are provided to highlight how political concepts pervade health.